2011
DOI: 10.3892/mmr.2011.686
|View full text |Cite
|
Sign up to set email alerts
|

Effects of leptin on the expression of fatty acid-binding proteins in human placental cell cultures

Abstract: Abstract. The present study aimed to evaluate the protein expression of the transmembrane translocase FAT/CD36 and cytoplasmic H-FABP and L-FABP in human trophoblast tissue and evaluate the effects of exogenous leptin upon differential expression of each biomolecule; consequently, it aimed to derive information regarding the effects of leptin upon the expression of proteins implicated in fatty acid metabolism. Protein and total RNA were isolated from 72 samples of trophoblast tissue obtained from chorionic vil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 18 publications
0
17
0
Order By: Relevance
“…Experimental studies have indicated a role of leptin in the regulation of the transfer of amino acids and lipids through the placenta 41, 42 ; however, the literature remains contradictory, and there is no consensus regarding the association between leptin concentrations and infant BW in humans. Our findings are in line with a study by Shrof et al .…”
Section: Discussionmentioning
confidence: 99%
“…Experimental studies have indicated a role of leptin in the regulation of the transfer of amino acids and lipids through the placenta 41, 42 ; however, the literature remains contradictory, and there is no consensus regarding the association between leptin concentrations and infant BW in humans. Our findings are in line with a study by Shrof et al .…”
Section: Discussionmentioning
confidence: 99%
“…The FABPs are responsible for cytosolic trafficking of FFAs to sites for esterification, beta-oxidation and subsequent transfer to the fetus [ 69 ]. The expression and activity of the proteins involved in fatty acid transport are influenced by insulin, IGF1 and leptin [ 70 , 71 , 72 ]. It remains unclear as to which step in the process limits the rate of placental fatty acid transport to the fetus.…”
Section: Placenta Nutrient Transportmentioning
confidence: 99%
“…Since proportionally less DHA and arachidonic acid is transferred to the fetus in IUGR pregnancies [132], but expression of FAT is unchanged [133], a role for FAT in selective LCPUFA transfer seems unlikely [134]. Little is known about regulation of pFABPpm and FAT in human placenta, but in cultured trophoblast cells, elevated levels of leptin cause an increase in FAT expression [87]. …”
Section: Fatty Acidsmentioning
confidence: 99%